Effect of fuel properties on spray breakup and evaporation studied for a multihole direct injection spark ignition injector - Zigan, Lars; Schmitz, Ingo; Flügel, Alexandre; Knorsch, Tobias; Wensing, Michael; Leipertz, Alfred (Energy & Fuels, 2010)
Mixture formation in spray-guided direct injection spark ignition engines (SG-DISI) with late injection timing is mainly controlled by spray atomization and evaporation and strongly depends on fuel properties. The influence of fuel composition on the liquid spray structure was determined for a 12-hole solenoid injector with integral and light sheet Mie scattering as well as phase Doppler anemometry (PDA). Late injection timing in a high pressure atmosphere was simulated in an injection chamber (1.5 MPa, 293 and 673 K) to characterize the spray propagation and evaporation of alkanes with high and low volatility (n-hexane, n-heptane, n-decane) and a 3-component mixture of these alkanes with similar fuel properties like gasoline fuel. Under high chamber pressure and low ambient temperature, the spray propagation and the resulting droplet sizes are similar for all fuels. However, for n-decane, the droplet size distribution is shifted to smaller droplets and the spray appeared to be less dense because of fuel-dependent internal nozzle flow which results in a reduced injected fuel mass. In contrast, under high ambient temperature conditions for more volatile fuel components, the liquid spray length is reduced and droplet size as well as droplet momenta are decreased. Small amounts of high boiling fractions delay the evaporation and support the overall spray stability also for multicomponent mixtures which is indicated by increased spray length as well as larger droplet sizes and momenta. Moreover, the droplet size distributions and the small liquid Peclet numbers (PeL ≈ 1) of the 3-component fuel indicate a demixing of light and heavy boiling components in the 3-component fuel under conditions which are typical for DISI strategies with late injection. © 2010 American Chemical Society.
Created from Fastlane, Scopus look-up